Energy Efficiency Enhancement and Climate Change Mitigations of SMEs through Grid-Interactive Solar Photovoltaic System - G. N. Lalith Pankaj Raj; V. Kirubakaran (International Journal of Photoenergy)
According to the International Energy Agency’s estimation, Indian primary energy demand is expected to increase by about 1250 Mtoe and 1500 Mtoe by 2030. The 3 M management concept now changed into a 4 M management concept that includes energy management. In the case of energy management, the electrical energy sector assumes critical importance. An energy cost occupies nearly 30-40% of the production cost in small and medium-size enterprises (SMEs). Bureau of Energy Efficiency (BEE) has initiated a separate energy efficiency intervention to the SME’s, where the energy-efficient technologies, operational procedures, and proper awareness programs to SMEs are stated. This paper discusses the complete electrical energy audit on a small-scale Siddha and Ayurveda medicine industry. The traditional medicine manufacturing technologies make the process complex (process loads are intermittent/interlinked) during analysis. Hence, the detailed energy auditing/conservation studies on the power factor/harmonics were carried out without affecting Indian traditional medicine manufacturing technology. The postauditing design and installation of an intelligent controller by considering the intermittent/interlinked loads are carried out, and the effectiveness of the intelligent controller is ascertained with the energy conservation and the carbon emission reduction of SME. In addition, the climate change mitigation is ensured through the design and deployment of grid-interactive rooftop solar photovoltaic power plant using Solar Pro v4.5 (Photovoltaic System simulation software) with the power analysis, economic analysis and life cycle carbon emission of the proposed plant. The proposed solar photovoltaic power plant ensures energy self-sufficiency and sustainable energy utilization by carbon emission reduction on electricity utilization of SMEs.